The effect of oxygen and nitrogen functional groups on the electrochemical performance of ordered carbon - Nur Izzatie Hannah, Razman; Salasiah, Endud; Izan Izwan, Misnon (Penerbit Universiti Teknologi Malaysia, 2019)
Ordered carbon (OC) has been synthesised via replication strategy by using Santa Barbara Amorphous (SBA)-15 as a template. The successful replication process has been proven by nitrogen adsorption-desorption analyzer and transmission electron microscopy (TEM). The OC showed well-aligned mesopore system, similar to the SBA-15 template. The oxygen and nitrogen functional groups introduced were identified by X-ray photoelectron spectroscopy (XPS). Electrochemical performance of the oxygen containing OC (OC-O), nitrogen containing OC (OC-N), and oxygen nitrogen containing OC (OC-ON) was then evaluated by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) using a three electrode system in 1M KOH aqueous electrolyte. The OC-O, OC-N, and OC-ON showed significant increment in specific capacitance, CS and exhibited good capacitance retention (CR, %) over high scan rate and current density.